Mass Production of Functional Amine–Conjugated PAN Nanofiber Mat via Syringeless Electrospinning and CVD. Issue 7 (11th May 2018) - Moon, Seongjun; Park, Kyueun; Seo, Eunbyeol; Lee, Kyung Jin
Abstract: Polymeric nanofiber webs have attained much attention because they can provide high surface area with various functional groups. To obtain the polymeric nanofiber webs, electrospinning is the most attractive method because this can provide the versatility of material selection. However, it is relatively difficult to obtain the nanofiber webs, which have highly reactive functional groups and high mechanical strength with high production rate. Here, the helically probed rotating cylinder (HPRC) system based on syringeless electrospinning and chemical vapor deposition (CVD) is introduced to prepare the polyacrylonitrile (PAN) nanofiber webs, having high functional groups and high mechanical strength in fast production rate. The HPRC system can provide the PAN nanofiber webs in high production rate, and the CVD process can provide high reactive functional groups on the PAN nanofiber. In addition, the nanofiber webs can be applied to diverse potential application fields, which require a high number of functional moieties. Abstract : The functional amine–conjugated PAN nanofiber mat is prepared in high production rate using syringeless electrospinning and chemical vapor deposition. The prepared nanofiber mat has high functionality that is induced by a high amount of amine functional groups on the fiber, and high mechanical property. Furthermore, the nanofiber mat can be used for a high‐reactive nanofiber platform.